Study Of Germ Numbers In Washing Tableware With Soaking Technique On Food Traders In Kelun Village, Madiun City - Siska Meilinda; Zaenal Abidin; Pipid Ari Wibowo (Journal of Social Research, 2024)
The purpose of this study was to determine and analyze the study of germ numbers in washing tools and soaking techniques in food traders in the Kelun village of Madison City. The method used in this research is descriptive, with a cross-sectional design. The population in this study were all food traders in Kelun Village; the type of sample used in this research was nonprobability sampling. The results showed that a comparative study of the number of germs based on the washing technique of cutlery of food traders in Kelun Village, Madiun City, showed that traders who used washing techniques through immersion had an average number of germs of 1.33 with a percentage of 100% not meeting the requirements. This study has implications for increasing awareness and knowledge of food vendors regarding the importance of effective washing techniques to maintain the cleanliness of cutlery. This study also emphasizes the need for education and training for food vendors on more hygienic washing methods, such as the use of running water and proper drying.